Minimum income in Portugal : changing the rules in times of crisis - Rodrigues, Carlos Farinha (2012)
The aim of this paper is to estimate the impact on the distribution of household income and poverty of the 2010 reform of the law that establish the non-contributory social benefits entitlement conditions in Portugal, with particular incidence in the Social Integration Income (RSI). Carried out in a period of serious deepening economic and social crisis, the changes in the resources condition appear fundamentally as a way of limiting and reducing the resources earmarked for social policies usage, precisely at the time when increased social insecurity should lead to a significant increase in the importance of such social policies. Using micro-data from the European Union Statistics on Income and Living Conditions (EU-SILC), we simulate the impact of the reform and estimate its effects on the income distribution and on different dimensions of monetary poverty. The change in the size of government expenditure required to finance these programs will also be estimated.